2002
DOI: 10.1002/arch.10043
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of Acmar1, a mariner‐like element in the asiatic honey bee, Apis cerana japonica (Hymenoptera, Apocrita)

Abstract: A mariner-like element was cloned from the genome of the Asiatic honey bee, Apis cerana japonica (Hymenoptera, Apocrita). The (composite) clone, named Acmar1, was 1,378 bp long, and encoded 336 amino acids corresponding to a transposase-like putative polypeptide in a single open reading frame. The D,D(34)D motif, the catalytic domain of the mariner transposase, was present, although there was a deletion of five amino acid residues within it as compared with the active transposase in Drosophila mauritiana. Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…As shown in Fig. 6, the TIRs reported by Sumitani et al (2002) were identified in all six Apis species, and most parts of the sequences of transposase-coding regions (underlined in green) plus these TIRs were similar between Apis species. Furthermore, although several indels were detected between the A. cerana species (Acc, Ack, and Acj) and Am, Ad, and Af in TIRs flanking outer regions, most parts of the sequences in the regions were conserved between the species, suggesting that the MLE eventually settled in this region in these Apis species.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…As shown in Fig. 6, the TIRs reported by Sumitani et al (2002) were identified in all six Apis species, and most parts of the sequences of transposase-coding regions (underlined in green) plus these TIRs were similar between Apis species. Furthermore, although several indels were detected between the A. cerana species (Acc, Ack, and Acj) and Am, Ad, and Af in TIRs flanking outer regions, most parts of the sequences in the regions were conserved between the species, suggesting that the MLE eventually settled in this region in these Apis species.…”
Section: Resultsmentioning
confidence: 79%
“…We searched long MLEs in the clade including multiple Apis MLEs that encode full-length transposases (sequences of more than 300 amino acids). We found Acc_MLE_100.p1, Acj_MLE_148.p1, and Ack_MLE_6.p1 in this clade and the sequences of these MLEs were identical, except for one residue, with 99% identity to “ Apis cerana Mariner transposase” in NCBI GenPept (Accession ID: BAB86288.1) (data not shown) (Sumitani et al 2002).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The putative transposase from S. invicta (Sinvmar1) contains five frameshifts and two stop codons, indicating that it is a defective copy (Krieger and Ross, 2003). Acmar1, a MLE from Apis cerana japonica (Hymenoptera, Apocrita) contained a sequence with the motif D,D(34)D but with a deletion of five amino-acid residues in the frame within the motif as compared to the corresponding sequence of D. mauritiana Mos1 (Sumitani et al, 2002). All the characteristics of the Mboumar elements analyzed appear to indicate that it is an active element; nevertheless, this needs to be confirmed by in vivo transposition assays or in vitro excision assays.…”
Section: Sequence Analysis Of the Mariner Element And Results Of Rt-pcrmentioning
confidence: 99%
“…Degenerate PCR primers based on the ITR sequences of other irritans subfamily members (Robertson and Lampe, 1995) were designed to obtain the full-length sequence of Apmar1. A similar method was used by Sumitami et al (2002) in Apis cerana, however, with no results. An earlier study (Bigot et al, 1994) reported the successful recovery of full-length mariner sequences from several hymenopteran members using PCR primers based on a consensus sequence of ITRs.…”
Section: Discussionmentioning
confidence: 99%